Abundance and Seasonality of Aedes aegypti (Diptera: Culicidae) in Two Suburban Localities of South Mexico, With Implications for Wolbachia (Rickettsiales: Rickettsiaceae)-Carrying Male Releases for Population Suppression. Issue 4 (2nd April 2021) - Che-Mendoza, Azael; Martin-Park, Abdiel; Chávez-Trava, Juan Manuel; Contreras-Perera, Yamili; Delfín-González, Hugo; González-Olvera, Gabriela; Leirana-Alcocer, Jorge; Guillermo-May, Guillermo; Chan-Espinoza, Daniel; Pavia-Ruz, Norma; Méndez-Vales, Rosa Eugenia; Alcocer-Gamboa, Alberto; et al.
Abstract: We conducted a baseline characterization of the abundance and seasonality of Aedes aegypti (Linnaeus, 1762)—a vector of dengue, chikungunya, and Zika—in two suburban localities of Yucatan, Mexico, as the first step in the implementation of an integrated vector management (IVM) plan combining 'traditional Aedes control' (source reduction/truck-mounted ultra-low volume [ULV] spraying) and incompatible insect technique/sterile insect technique for population suppression in Yucatan, Mexico. Weekly entomological collections with ovitraps and BG-sentinel traps were performed in 1-ha quadrants of both localities for 1 yr. Three distinct periods/phases were identified, closely associated with precipitation: 1) a phase of low population abundance during the dry season (weekly average of Aedes eggs per ovitrap and adults per BG trap = 15.51 ± 0.71 and 10.07 ± 0.88, respectively); 2) a phase of population growth and greatest abundance of Aedes (49.03 ± 1.48 eggs and 25.69 ± 1.31 adults) during the rainy season; and finally 3) a phase of decline among populations (20.91 ± 0.97 eggs and 3.24 ± 0.21 adults) after the peak of the rainy season. Seasonal abundance and dynamics of Ae. aegypti populations suggest that it is feasible to develop and implement time-specific actions as part of an IVM approach incorporating integrating novel technologies (such as rear-and-release of Wolbachia -infected males) with classic (insecticide-based) approaches implemented routinely for vector control. In agreement with the local vector control program, we propose a pilot IVM strategy structured in a preparation phase, an attack phase with traditional vector control, and a suppression phase with inundative releases, which are described in this paper.